2020
DOI: 10.1177/1010539520944721
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Self-Reported Periodontitis in Japanese Adults: The Japan Public Health Center–Based Prospective Study for the Next-Generation Oral Health Study

Abstract: This study evaluated the validity of self-reported periodontitis measures among 2404 Japanese adults aged 40 to 75 years. A self-administered questionnaire survey and a clinical periodontal examination were conducted from 2013 through 2016. The self-reported periodontitis questions included 3 sociodemographic, 3 health, and 5 periodontal health–related items. Based on the clinical case definition of periodontitis, 26.5% of participants were found to be periodontally healthy, 2.7% had mild periodontitis, 55.2% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Systematic reviews evaluating the validity of a questionnaire and/or self-reported measures for periodontal diseases, including gingivitis screening, have concluded that self-perceived pathologies were somewhat more specific (SP) than sensitive (SN) [11,12]. The same results were recently found by Ueno et al and Saka-Herran et al [14,52], with higher specificity than sensitivity, even if sensitivity was remarkably high in the latter study. For a given item, sensitivity and specificity depend on the cut-off used to define the bleeding and on how the gingival bleeding is evaluated, which is specific to each study.…”
Section: Discussionsupporting
confidence: 60%
“…Systematic reviews evaluating the validity of a questionnaire and/or self-reported measures for periodontal diseases, including gingivitis screening, have concluded that self-perceived pathologies were somewhat more specific (SP) than sensitive (SN) [11,12]. The same results were recently found by Ueno et al and Saka-Herran et al [14,52], with higher specificity than sensitivity, even if sensitivity was remarkably high in the latter study. For a given item, sensitivity and specificity depend on the cut-off used to define the bleeding and on how the gingival bleeding is evaluated, which is specific to each study.…”
Section: Discussionsupporting
confidence: 60%
“…All participants in this study showed negative screening results, as assessed by the authors, and showed no subjective symptoms of periodontal disease. Furthermore, in Japan, in the age group corresponding to the age group of the healthy individuals included in this study (median age: 31.0 years), only 32.4% individuals had periodontal pockets with depths of 4 mm or more [ 38 ]. Our identification of Cit-CK13 is unlikely to be related to periodontal disease, since it was detected in all healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the DCA supports the use of the tool in identifying individuals with high risk of SP. Most of the published validation studies were conducted mainly in the Western population [ 14 , 15 , 17 , 20 , 21 , 22 , 23 ] with a few exceptions conducted in the East Asian population [ 27 , 28 ]. None has been conducted in a population such as ours, with a multi-ethnic mix of Chinese, Malays and Indians.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the validity of self-reporting for periodontitis has been tested in different Western populations [ 14 , 15 , 20 , 21 , 22 , 23 ], including high-risk populations in rural areas [ 24 ], African Americans [ 25 ] and post-partum women [ 26 ]. Very few studies have been carried out in Asian populations, mainly in China [ 27 ] and Japan [ 28 ]. In addition, validation studies based on the new periodontitis classification (World Workshop on the Classification of Periodontal and Peri-implant Diseases and Conditions (WWC)) [ 29 ] are sparse [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%